125k views
4 votes
Solve the equation 3p (3p - 8) - 8 = 9p ( p - 3 + 4

User Benhatsor
by
5.9k points

2 Answers

4 votes

Answer:

p = 4

Explanation:

3p (3p - 8) - 8 = 9p (p - 3) + 4

9p² - 24p - 8 = 9p² - 27p + 4

3p = 12

p = 4

5 votes

Answer:


p= (-8)/(33)

Explanation:

Given:


3p (3p - 8) - 8 = 9p ( p - 3 + 4)

To Find:

Value of p=?

Solution:

Before solving this equation, we will use the method of BODMAS which states that we first solve the Bracket then Off then Division then Multiplier then addition and at last subtraction.

Now we will solve the both right and left hand side of the equation


3p (3p - 8) - 8 = 9p ( p - 3 + 4)


9p^2-24p-8=9p^2+9p

Gruoping the like terms we get,


9p^2-9p^2-24p-9p=8

After solving the both right hand and left hand side of the equation


-33p=8

And we get the value of p as


p= (-8)/(33)

User Rob Myrick
by
5.8k points